Pengaruh Kombinasi Daun Katuk dan Daun Kacang Panjang terhadap Produksi ASI: The Effect Of The Combination of Katuk Leaf and Leather of Bean Long on Breast Milk Production - Fajrin, Dessy Hidayati; Desy Rosita; Surtalia Nainggolan (Universitas Ngudi waluyo, 2023)
Exclusive breastfeeding (ASI), according to the World Health Organization, so pregnant women and mothers who have just given birth are informed about the benefits and advantages of breastfeeding, where it is the best nutrition and protection against disease. Exclusive breastfeeding coverage in the working area of the Lumar District Health Center, Bengkayang Regency, has not been achieved. Lack of nutrition causes significant losses for babies, especially growth and development problems that can experience stunting. Vegetables that can increase the volume of breast milk include katuk leaves and long bean leaves. This study aimed to find out how